Analysis of the Company's Bankruptcy Rate using the Altman Z-Score and Grover Methods on Agricultural Companies Listed on the Indonesia Sharia Stock Index in 2019-2021 - Hartomi Maulana; Zaki Rosyadi; Soritua Ahmad Ramdani Harahap (Universitas Darussalam Gontor, 2024)
The Covid-19 pandemic hit global stock markets, including Indonesia. As a result, all sectoral indexes experienced a decline in their financial performance, especially the agricultural sector in the Indonesian Sharia Stock Index. This study used quantitative research. The population was obtained from 17 agricultural sector industrial companies registered with ISSI with a sample of 12 companies. The result of this study is that there are differences in score results in each bankruptcy prediction analysis method for 3 periods. The Altman Z-Score method in 2019 predicts 8 companies will be declared bankrupt and 4 companies are declared in good health. In 2020, the Altman Z-Score method predicts that 7 companies will be declared bankrupt and 5 companies will be declared in good health. In 2021, the Altman Z-Score method predicts that 7 companies will be declared bankrupt and 5 companies will be declared in good health. Grover's method in 2019 predicts that 3 companies will be declared bankrupt and 9 companies will be declared in good health. In 2020, Grover's method predicts that 3 companies will be declared bankrupt and 9 companies will be declared in good health. In 2021, Grover's method predicts that no company will be declared bankrupt and 12 companies will be declared in good health. It can be concluded that the Altman Z-Score method is considered optimal in this study to predict bankruptcy rates, assuming aspects of the Altman Z-Score method that highlight the company's profitability so as to affect the deeper accuracy of the company's financial performance.